Genome-wide investigation and characterization of heat shock transcription factors in papaya (Carica papaya): Mining of the HSF transcription factor in papaya - Le, Thi Man; Azar, Sahar; Thi Thanh Tran, Huyen; Chu, Ha Duc; Vu, Quyen Thi Xuan; Tran, Lan Thi Mai; La, Hong Viet; Le, Chi Toan; Cao, Phi Bang (Journal of Tropical Life Science, 2024)
Heat shock transcription factors (Hsf-s) have been considered one of the major regulatory proteins that play important roles in various biological processes during the growth and development of plants. Unfortunately, no comprehensive studies of the Hsf family in papaya (Carica papaya), a popular tropical fruit crop, have been performed, even the papaya genome assembly has been released recently. In this study, a total of 18 members of the Hsf family, namely CpHsf-s have been identified in papaya. Based on various computational tools, a systematic characterization of the CpHsf family, such as gene structure, physic-chemical features, categorization, and protein-protein interaction, has been conducted. We found that the physic-chemical properties of the CpHsf proteins were highly variable, while all proteins were hydrophilic and localized in the nucleus. Our classification indicated that the CpHsf proteins could be categorized into three groups, including HsfA, HsfB, and HsfC, and members in the same clade share similar gene structure. According to the previous RNA-Seq datasets, our re-analysis revealed that the CpHsf genes exhibited different expressions in various major organs or tissues during fruit ripening and under the ultra-low temperature stress. Taken together, our study could provide a list of candidate genes for further functional characterization towards the improvement of stress tolerance in papaya.